2021
DOI: 10.1007/s40256-021-00493-7
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Initiation of Sotalol in Patients with Atrial Fibrillation: Utility of Cardiac Implantable Electronic Devices for Therapy Monitoring

Abstract: Background Antiarrhythmic drugs are often used in the management of patients with atrial fibrillation (AF). Sotalol is conventionally initiated in the inpatient setting for monitoring efficacy and adverse effects, including QTc interval prolongation and torsades de pointes (TdP) proarrhythmia. Objective We aimed to evaluate the efficacy and safety of outpatient initiation of sotalol for the treatment of AF in a select group of patients with cardiac implantable electronic devices (CIEDs): permanent pacemakers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Most importantly, close monitoring for arrhythmic events is paramount to ensure patient safety. Mascarenhas et al 19 used the remote monitoring capabilities of CIEDs for safe outpatient initiation of sotalol in their group of patients. The QT interval was assessed from intracardiac electrograms and ECG tracings obtained via manual transmission from the CIEDs at 2-hour post-sotalol dosing, and patients were seen daily for the first 3 days with 12-lead ECGs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, close monitoring for arrhythmic events is paramount to ensure patient safety. Mascarenhas et al 19 used the remote monitoring capabilities of CIEDs for safe outpatient initiation of sotalol in their group of patients. The QT interval was assessed from intracardiac electrograms and ECG tracings obtained via manual transmission from the CIEDs at 2-hour post-sotalol dosing, and patients were seen daily for the first 3 days with 12-lead ECGs.…”
Section: Discussionmentioning
confidence: 99%
“…16 These requirements result in significant economic implications in using this strategy, with a reported hospitalization cost between US$3278 and US$12,466, mainly because of the cost of the hospital room itself. 17 , 18 More contemporary studies have suggested the safety of outpatient initiation of sotalol therapy in patients with implantable cardiac devices 19 and no excess mortality in patients treated with sotalol compared with β-blockers. 20 Here, we aim to determine the safety aspects of sotalol initiation in outpatient settings without continuous rhythm monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some centers, particularly those outside of the United States, have implemented novel protocols for outpatient sotalol loading that employ ambulatory cardiac monitoring (e.g., cardiac event monitors, or implantable electronic pacemaker or defibrillator data) to monitor for ECG abnormalities such as QT prolongation and ventricular ectopy in the outpatient setting while loading patients with sotalol. 19 If these novel approaches for outpatient sotalol loading prove safe and effective, then they may provide viable and cost‐effective alternatives to both oral and IV inpatient loading protocols. Additional studies will be needed on both IV sotalol and these novel outpatient oral sotalol loading strategies to determine the feasibility, efficacy, safety, and costs associated with each to determine the optimal drug formulation and loading protocols for this medication.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial arrhythmias in patients with CHD are associated with increased rates of heart failure, sudden death, stroke, and hospitalization. 5 Rhythm control is preferred over rate control in more complex forms of CHD 6 ; however, the currently available agents either have a poor side effect profile, 7 require intensive monitoring at initiation, or may increase all-cause mortality. 8 Catheter ablation of atrial tachycardia (AT) in patients with CHD is known to be safe and effective.…”
mentioning
confidence: 99%